KEBIJAKAN PELAYANAN E-KTP (STUDI TENTANG KUALITAS PELAYANAN E-KTP Di KECAMATAN RUNGKUT) - Taufiq, Nur (Universitas 17 Agustus 1945 Surabaya, 2017)
The quality of public service of making e-ID card is a form of public service needed by society as personal identity. In the context of making e-ID card in Rungkut District Office of Surabaya City still found the complaints of the community. These complaints include the timing of incorrect e-ID card making. The formulation of the problem in this research is